Renin angiotensin system and cardiac hypertrophy after sinoaortic denervation in rats - Piratello, Aline Cristina [UNIFESP] (2010)
OBJECTIVE: The aim of this study was to evaluate the role of angiotensin I, II and 1-7 on left ventricular hypertrophy of Wistar and spontaneously hypertensive rats submitted to sinoaortic denervation. METHODS: Ten weeks after sinoaortic denervation, hemodynamic and morphofunctional parameters were analyzed, and the left ventricle was dissected for biochemical analyses. RESULTS: Hypertensive groups (controls and denervated) showed an increase on mean blood pressure compared with normotensive ones (controls and denervated). Blood pressure variability was higher in denervated groups than in their respective controls. Left ventricular mass and collagen content were increased in the normotensive denervated and in both spontaneously hypertensive groups compared with Wistar controls. Both hypertensive groups presented a higher concentration of angiotensin II than Wistar controls, whereas angiotensin 1-7 concentration was decreased in the hypertensive denervated group in relation to the Wistar groups. There was no difference in angiotensin I concentration among groups. CONCLUSION: Our results suggest that not only blood pressure variability and reduced baroreflex sensitivity but also elevated levels of angiotensin II and a reduced concentration of angiotensin 1-7 may contribute to the development of left ventricular hypertrophy. These data indicate that baroreflex dysfunction associated with changes in the renin angiotensin system may be predictive factors of left ventricular hypertrophy and cardiac failure.